Acetaldehyde, Not Ethanol, Impairs Myelin Formation and Viability in Primary Mouse Oligodendrocytes. (19th February 2015) - Coutts, David J. C.; Harrison, Neil L.
Abstract : Background: Excessive ethanol (EtOH) drinking is associated with white matter loss in the brain at all stages of life. Myelin‐forming oligodendrocytes (OLs) are a major component of white matter, but their involvement in EtOH‐mediated white matter loss is unclear. Myelination continues throughout the life with highest rates during fetal development and adolescence. However, little is known about the effects of EtOH and its principal metabolite acetaldehyde (ACD) on OLs at the cellular level. Methods: We compared the responses to different concentrations of EtOH or ACD by primary OLs in culture. Results: EtOH did not cause significant cell death at concentrations lower than 120 mM, even after 24 hours. In comparison, ACD was highly lethal at doses above 50  μ M. High concentrations of EtOH (120 mM) and ACD (500  μ M) for 24 hours did not reduce myelin in mature OLs. Myelin production and OL differentiation were significantly impaired by 7 days exposure to 500 or 50  μ M ACD but not 120 mM EtOH. Conclusions: This study shows that OLs are relatively resistant to EtOH, even at a concentration more than 4 times the typical blood EtOH concentrations associated with social drinking (10 to 30 mM). In contrast, OLs are much more sensitive to ACD than EtOH, particularly with long‐term exposure. This suggests that part of white matter loss in response to EtOH, especially during high rates of myelin formation, may be due in part to the effects of its principal metabolite ACD.